ETHNIC BELONGING OF THE UZBEK POPULATION (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
Clinically important genes СYP1А1, СYP2С9, СYP3А4 were studied for the first time in 217 healthy volunteers in Uzbek population. The frequencies of minor alleles СYP1А1*2С, СYP2С9*2, СYP3А4*1В were 6.7, 9.4, and 3.2%, respectively and corresponded to those in the Caucasians. For 3 alleles the genotype frequencies were in accordance with Hardy–Weinberg equilibrium. The absence of homozygous СYP1А1*2С, СYP2С9*2, СYP3А4*1В was revealed. Of 217 persons 86.6, 81.1, and 93.5% were homozygous for wild alleles, 13.4, 18.9 и 6.5% were heterozygotes for СYP1А1*2С, СYP2С9*2, СYP3А4*1В, respectively. The observed heterozygotes were shown to prevail over the expected ones for СYP1А1*2С, СYP2С9*2.